2010
DOI: 10.1093/treephys/tpq039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbohydrate supply on stem growth, wood and respired CO2  13C: assessment by experimental girdling

Abstract: The present study examines the impact of the C source (reserves vs current assimilates) on tree C isotope signals and stem growth, using experimental girdling to stop the supply of C from leaves to stem. Two-year-old sessile oaks (Quercus petraea) were girdled at three different phenological periods during the leafy period: during early wood growth (Girdling Period 1), during late wood growth (Girdling Period 2) and just after growth cessation (Girdling Period 3). The measured variables included stem respirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 55 publications
4
55
0
Order By: Relevance
“…Carry-over effects of stored products in tree ring formation from one year to the next were also detected by Helle and Schleser (2004) and Keel et al (2007). However, as demonstrated by several authors (Maunoury-Danger et al 2010;Maier et al 2010) a seasonal shift in substrate use from reserves to recently fixed carbohydrate during active radial growth might occur.…”
Section: Discussionmentioning
confidence: 69%
“…Carry-over effects of stored products in tree ring formation from one year to the next were also detected by Helle and Schleser (2004) and Keel et al (2007). However, as demonstrated by several authors (Maunoury-Danger et al 2010;Maier et al 2010) a seasonal shift in substrate use from reserves to recently fixed carbohydrate during active radial growth might occur.…”
Section: Discussionmentioning
confidence: 69%
“…While some girdling studies indicated that NSC reserves in the stem were not sufficient to sustain growth below the girdle in the short term or the long term (de Schepper et al, 2010;Maier et al, 2010), others demonstrated that stem reserves could be used to restart growth (Daudet et al, 2005; Maunoury-Danger et al, 2010). This assumption imposes source-sink relationships between xylem ray parenchyma cells and living cells (Olano et al, 2013).…”
Section: The Role Of Tissue In Supplying Nscsmentioning
confidence: 99%
“…Reserves often are used at growth resumption in early spring (Oribe et al, 2003;Begum et al, 2013), but most xylem is formed with newly synthesized NSCs Beck, 1990, 1994;Kagawa et al, 2006). The ray parenchyma cells in xylem also could act as a source of NSCs to sustain growth when assimilates coming from the leaf become scarce (Maunoury-Danger et al, 2010;Olano et al, 2013), such as during a water deficit. As the molecular networks driving cell division and expansion largely rely on the availability of carbohydrates to provide energy and biomass (Lastdrager et al, 2014), xylem formation is an ideal system in which to study sourcesink relationships and the C dependence of growth metabolism.…”
mentioning
confidence: 99%
“…Stem girdling, as one of the most practical methods to provoke artificial stress (Stone 1974;Wilson 1998), was broadly used over the decades in horticulture to manage the growth and reproduction of several deciduous and evergreen tree species (Weinburger and Cullinan 1932;Lilleland and Brown 1936;Crane and Campbell 1957;Lewis and McCarty 1973;Winkler et al 1974;Powell and Cash Howell 1985;Fernandez-Escobar et al 1987;Augusti et al 1998;Day and DeJong 1999;Rivas et al 2008). Girdling has been practiced in the forestry and logging industry as a pre-harvest treatment to change wood properties (MacDougal 1943;Noel 1970;Lopez et al 2015) by manipulating annual ring width, wood density, duration of cambial activity, and latewood production (Wilson and Gartner 2002;Domec and Pruyn 2008;Maunoury-Danger et al 2010;Sellin et al 2013). More recently, several researchers have applied girdling for physiological experiments primarily to manipulate carbohydrate distribution within plants (De Schepper and Steppe 2011) and to study phloem-xylem interactions (Fishman et al 2001;Wilson and Gartner 2002;Zwieniecki et al 2004;Salleo et al 2006;Morandi et al 2007;Domec and Pruyn 2008;Tombesi et al 2014).…”
Section: Introductionmentioning
confidence: 99%